Experimental study and mechanism analysis of high-pressure water jet for mud cake cutting during shield tunneling - Ji, Fuquan; Liu, Pengfei; Yang, Zhao; Wen, Bowei; Hu, Qinxin (Frontiers in Earth Science, 2024)
When the opening rate of the cutter head of tunnel boring machines is insufficient for the removal of excavated soil in a timely manner, the soil tends to accumulate in front of the cutter head and inside the earth or slurry chamber, leading to mud caking. High-pressure water jetting is an effective method for removing mud cakes. This study explored the influence of high-pressure water jet parameters on the efficiency of mud cake cleaning by using highly weathered argillaceous siltstone as experimental materials. Mud cake compaction equipment and high-pressure water jetting devices were developed. In addition, the impact of jetting parameters such as jet pressure and flow rate on the mud cake cutting performance was investigated. The results indicated that with an increase in the erosion distance, the cutting width of the mud cake first increased and then gradually decreased to zero, while the cutting depth progressively diminished. Under the same jet pressure, when the flow rate increased from 49.1 L/min to 110 L/min, the cutting width of the high-pressure water jet increased. With further increase in the flow rate from 110 L/min to 202.8 L/min, the cutting width decreased and the cutting depth increased. Under the same jet flow, the increase in water pressure resulted in greater cutting width and depth.